Electrical characterization of a buried GaSb p‐n junction controlled by native defects. Issue 8 (30th June 2014) - Gorni, M.; Parisini, A.; Gombia, E.; Baldini, M.; Vantaggio, S.; Ghezzi, C.
<x xml:space="preserve">Abstract</x> Thanks to its absorption properties, GaSb is one of the best candidates for TPV and 3rd gen PV applications. A buried GaSb junction in a GaAs/GaSb heterostructure has been obtained by growing a heavily Zn doped GaAs epitaxial layer on a n‐type GaSb substrate, where Zn impurities diffuse. Current‐voltage characteristics show interesting rectification properties, however the formation of the junction resulted to be mainly controlled by an enhancement of the native defect GaSb rather than Zn. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>